Experimental investigation and thermodynamic re-assessment of the ternary copper-nickel-lead system. (June 2018) - Tesfaye, Fiseha; Vaajamo, Iina; Hamuyuni, Joseph; Lindberg, Daniel; Taskinen, Pekka; Hupa, Leena
Abstract: Due to their high corrosion resistance and thermal stability, Cu-Ni-alloys have essential role in many materials engineering applications. Lead is an alloying element in these alloys although it may also be considered as an impurity in certain cases. In copper rich alloys, lead tends to diffuse into the grain boundaries and weaken the hot-working properties. In addition to alloys design, accurate knowledge of phase relations and solubilities in the ternary Cu-Ni-Pb system has important role in improving the copper and nickel smelting and refining processes. In the present work, an isothermal equilibration technique was used to measure the mutual solubilities of liquid lead and solid CuNi foil in the temperature range 1280–1530 K. The samples were equilibrated and an Inductively Coupled Plasma Atomic Emission Spectrometer (ICP-AES) and an Electron Probe Micro Analyzer (EPMA) were used to quantify the chemical composition of the phases. Selected solubility data obtained in this work were combined with the literature data to obtain a thermodynamic description of the Cu-Ni-Pb ternary liquid and fcc solid solution phases by applying the CALPHAD method. The ternary assessment agrees well with the experimental observations in this work.